Dietary and physical activity risk and protective factors for lean non-alcoholic fatty liver disease: a scoping review - Corrigan, Joanne (Kansas State University, 2024)
Non-Alcoholic Fatty Liver Disease (NAFLD) is one of the most common causes of chronic liver disease globally and describes a spectrum of conditions ranging from simple hepatic steatosis to liver cirrhosis and/or failure. Although it is more prevalent in populations with metabolic risk factors including obesity, insulin resistance, dyslipidemia, and type 2 diabetes, it can also occur in lean populations who may or may not present with symptoms of NAFLD. Consequently, lean populations with NAFLD can be overlooked in both clinical and research settings. Despite the associations between diet and physical activity and the prevention of many chronic diseases, primary research exploring the association between diet and physical activity and NAFLD risk in lean populations is lacking. The purpose of this scoping review was to describe the available research on dietary and physical activity risk and protective factors in lean NAFLD, define key terms related to this condition, and identify knowledge gaps to inform future research. A literature search was conducted between March 2021 and August 2023 in PubMed, Global Health, ProQuest Nursing and Allied Health, Web of Science, and Scopus. Sixty-four articles were included in the review. The predominant study designs were cross-sectional and prospective. More than half of the studies were based in Asia. Research topics included the associations between specific diets, food groups, macronutrients, micronutrients, beverages, and varying physical activity characteristics, and lean NAFLD risk. Very few definitive conclusions could be made about potential dietary or physical activity risk and protective factors for lean NAFLD due to several limitations in the current body of evidence. These limitations included a high risk for bias and lack of ethnic diversity in study populations, as well as significant heterogeneity in results, definitions of key terms, and NAFLD diagnostic criteria. To address these deficits, future research is needed on topics explored in the current body of evidence, using higher quality study designs that limit the risk of bias, integrate more ethnic diversity in study populations, and implement consistent terminology and NAFLD diagnostic criteria.
Keywords: Non-alcoholic fatty liver disease; Lean; Dietary risk factors; Physical activity risk factors; Normal weight